Which expressions are equivalent to -6+3(2+(-4t))−6+3(2+(−4t))minus, 6, plus, 3, left parenthesis, 2, plus, left parenthesis, minus, 4, t, right parenthesis, right parenthesis ? Choose all answers that apply: Choose all answers that apply: (Choice A)

Respuesta :

Answer:

-6+3(2+(-4t)) = -12t

Step-by-step explanation:

The given expression is :

-6+3(2+(-4t))

We need to find the equivalent expression for this.

Firstly, we open parenthesis.

= -6+3[2-4t]

= -6 + 3(2) +3(-4t)

= -6 + 6 -12t

= -12t

The equivalent expresssion for the given expression is (-12t).

Answer:

THE ANSWER IS C

Step-by-step explanation:

IF YOU ARE HERE FOR KHAN ACADEMY

YOU ARE VERY WELCOME

ACCESS MORE